2016
DOI: 10.18552/2016/scmt4m110
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Recycled Nylon Fibers in Mortar Comparing with Recycled PET and PVA Fibers

Abstract: In this study, the authors focused on the potential and efficiency of recycled nylon fibers obtained from waste fishing nets as tensile reinforcement of mortar, and discussed comparisons with the experimental results of recycled PET and PVA fibers. The recycled nylon fibers were obtained through manual cutting of waste fishing net at different lengths of 20 mm, 30 mm and 40 mm, and mixed in mortar with the volumes of 1.0%, 1.5% and 2.0%. It was observed that recycled nylon fibers significantly enhances the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, the effects of fibers on the R c of concrete need to be thoroughly clarified. On the other hand, almost all previous studies have reported an increase in R f [5,12,22,24,26] and R it [23,25] with the inclusion of fibers. But the proportion of fiber plays a crucial role here; up to a certain proportion of fiber, R f and R it increase, and with a further increase in fiber dosage, there is a decrease in strength due to its balling problem and uneven distribution [5].…”
Section: Authors Control MIX R C (Mpa) R C (Mpa) Aspect Ratio Fiber D...mentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, the effects of fibers on the R c of concrete need to be thoroughly clarified. On the other hand, almost all previous studies have reported an increase in R f [5,12,22,24,26] and R it [23,25] with the inclusion of fibers. But the proportion of fiber plays a crucial role here; up to a certain proportion of fiber, R f and R it increase, and with a further increase in fiber dosage, there is a decrease in strength due to its balling problem and uneven distribution [5].…”
Section: Authors Control MIX R C (Mpa) R C (Mpa) Aspect Ratio Fiber D...mentioning
confidence: 79%
“…[6] documented a 41% rise, and Ref. [24] showed a 41.56% rise in flexural strength as a result of incorporating fibers.…”
Section: Mechanical Properties In Hardened Statementioning
confidence: 95%